1965
DOI: 10.1021/bi00879a014
|View full text |Cite
|
Sign up to set email alerts
|

Identity of the Site of Action of 3',5'-Adenosine Monophosphate and Adrenocortocotropic Hormone in Corticosteroidogenesis in Rat Adrenal and Beef Adrenal Cortex Slices*

Abstract: In addition, neither 3',5'-AMP nor ACTH stimulated the transformation of [7a-3H]pregnenolone (3/3-hydroxy-5-pregnen-3-one) or [7-3H]progesterone (4-pregnene-3,20-dione) to corticosteroids. The results indicate that both 3',5'-AMP and ACTH stimulate at the same site in the biosynthetic pathway for corticosteroids, i.e., between cholesterol and pregnenolone, and suggest that 3 ',5 '-AMP is an obligatory intermediate in the action of ACTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

1967
1967
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(46 citation statements)
references
References 16 publications
3
43
0
Order By: Relevance
“…Since those early observations, many studies have indicated that the true rate limiting step effected by hormone stimulation is the delivery of the substrate for all steroid hormones, cholesterol, from the outer to the inner mitochondrial membrane and the P450scc enzyme (Karaboyas et al, 1965;Simpson et al, 1979;Crivello and Jefcoate, 1980;Privalle et al, 1983;Jefcoate et al, 1987). Diffusion of the hydrophobic cholesterol through the aqueous intermembrane space is extremely slow (Rennert et al, 1993) and, therefore, it became clear that the transfer of cholesterol from the outer membrane to the P450scc occurs in an assisted manner and that this is the rate limiting step.…”
Section: Acute Regulation Of Steroid Hormone Biosynthesismentioning
confidence: 99%
“…Since those early observations, many studies have indicated that the true rate limiting step effected by hormone stimulation is the delivery of the substrate for all steroid hormones, cholesterol, from the outer to the inner mitochondrial membrane and the P450scc enzyme (Karaboyas et al, 1965;Simpson et al, 1979;Crivello and Jefcoate, 1980;Privalle et al, 1983;Jefcoate et al, 1987). Diffusion of the hydrophobic cholesterol through the aqueous intermembrane space is extremely slow (Rennert et al, 1993) and, therefore, it became clear that the transfer of cholesterol from the outer membrane to the P450scc occurs in an assisted manner and that this is the rate limiting step.…”
Section: Acute Regulation Of Steroid Hormone Biosynthesismentioning
confidence: 99%
“…Regardless of tissue origin, however, a common feature of all steroid hormones is that their synthesis utilizes a common precursor, namely, cholesterol. In fact, it is the delivery of cholesterol to the site of its first enzymatic conversion that constitutes the rate-limiting and hormonally regulated step in steroidogenesis (Karaboyas & Koritz 1965, Brownie et al 1972, Simpson et al 1979, Crivello & Jefcoate 1980, Privalle et al 1983, Jefcoate et al 1987. In general terms, cellular cholesterol residing in the outer mitochondrial membrane, lipid droplets or plasma membranes of steroidogenic cells, must be delivered to the inner mitochondrial membrane, the site of the cytochrome P450 side chain cleavage enzyme (P450scc) which converts cholesterol to pregnenolone, the first steroid formed in all steroidogenic tissues.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that the rapid 1916 stimulation of steroid biosynthesis following an acute injection of ACTH is primarily the result of an increased rate of conversion of cholesterol to A5-pregnenolone (4,5). The A5-pregnenolone thus formed is converted in sequence to progesterone, deoxycorticosterone, and corticosterone by the rat adrenal, a process that is not influenced to a major degree by ACTH over short time intervals (5).…”
Section: Introductionmentioning
confidence: 99%
“…The A5-pregnenolone thus formed is converted in sequence to progesterone, deoxycorticosterone, and corticosterone by the rat adrenal, a process that is not influenced to a major degree by ACTH over short time intervals (5). The acute effect of ACTH can be blocked by a variety of inhibitors of protein synthesis (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation